Pengaruh komposisi campuran kotoran sapi dan limbah cair tapioka terhadap biogas yang dihasilkan - Agus Subakti; Dwi Irawan; Mafruddin Mafruddin; Sulis Dri Handono (Universitas Muhammadiyah Metro, 2022)
The depletion of fossil energy in the world is getting attention, this is due to the increasing number of human resources in the world. So that efforts can be made, one of which is finding alternative fuels, namely biogas made from cow dung and tapioca liquid waste, this study aims to determine the variation of the filling mixture on the volume of biogas produced, to know the variation of the filling mixture on the biogas flame and to determine the effect of the mixture variation. charge to the amount of flow rate produced. The research method used is bulk filling with cow dung and tapioca liquid waste using a mixed variation of 0%:100%, 10%:90, 20%: 80%, 30%: 70%, 40%: 60%, 50 % : 50%. So that the value of the volume of gas produced is proportional to the productivity of biogas. To find out the volume of biogas in the digester using a manometer U. In the study, the results obtained were the value of the filling mixture variation in biogas productivity for the highest value at the mixed variation of 50%: 50% with a value of 2.061 liter/kg. The highest blue RGB flame was obtained at a mixed variation of 70% : 30% with a value of 66.14 and a red RGB flame value was obtained at a mixed variation of 50% : 50% with a value of 42.14.